PENGARUH TERAPI AUTOGENIK TERHADAP TINGKAT KECEMASAN PASIEN PRE OPERASI DENGAN SPINAL ANESTESI - Rizky Fadillah Akbar; Marta Tania Gabriel Ching Cing; Wahyu Riyaningrum; Tati Hardiyani (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Preoperative anxiety is a common psychological problem experienced by patients prior to surgery, especially those undergoing spinal anesthesia. If left untreated, anxiety can affect physiological stability and increase the risk of perioperative complications. One non-pharmacological intervention to reduce anxiety is autogenic relaxation therapy. This study aimed to determine the effect of autogenic relaxation therapy on anxiety levels in preoperative patients undergoing spinal anesthesia. The study employed a pre-experimental one-group pretest–posttest design involving 32 patients selected through purposive sampling. Anxiety levels were measured using the Amsterdam Perioperative Anxiety and Information Scale (APAIS) before and after the intervention. Data were analyzed using the Shapiro–Wilk test and paired t-test. The results showed a significant reduction in anxiety levels after therapy (p = 0.001). In conclusion, autogenic relaxation therapy is effective and safe for reducing preoperative anxiety in patients undergoing spinal anesthesia.